An ex vivo evaluation of the efficacy of andrographolide in modulating differential expression of transcription factors and target genes in periodontal cells and its potential role in treating periodontal diseases. (20th January 2017) - Ambili R,; Janam, Prasanthila; Saneesh Babu, P.S.; Prasad, Manu; Vinod, D.; Anil Kumar, P.R.; Kumary, T.V.; Asha Nair, S.; Radhakrishna Pillai, M.
Abstract: Ethanopharmacological relevance: Andrographolide is a herbal extract traditionally used in South Asian countries for treating inflammatory diseases. Aim of the study: To evaluate the efficacy of andrographolide in management of periodontal disease which is a highly prevalent oral disease. Materials and Methods: Periodontal ligament fibroblasts (PDLF) were cultured from healthy and diseased periodontium using explant culture methods. The safe dose of AG was determined using MTT assay. LPS (lipopolysaccharide) of the most important periodontopathogen, P gingivalis was used to activate NF-κB and STAT3 in PDLF. The efficacy of AG in inhibiting NF-κB and STAT3 was analyzed using immunofluorescence. Down regulation of expression of target genes of these transcription factors related to inflammation and bone resorption were analyzed using real time PCR. Results: AG up to the concentration of 25 μM was found to be safe as determined by MTT assay. Statistically significant activation of NF-κB and STAT3 in cultured PDLF was observed in diseased group compared to healthy controls before and after LPS challenge. 5 μM AG pretreatment significantly inhibited activation of NF-κB and STAT3 and down regulated expression of inflammatory and bone resorptive genes in cultured PDLF. Conclusions: The findings of the present study propose the adjunctive use of a novel herbal drug andrographolide as a promising host modulation agent for periodontal therapy by inhibiting NF-κB and STAT3 activation and inhibition of inflammation and bone resorption related genes. Graphical abstract: